REABILITAÇÃO CARDÍACA EM INDIVÍDUO PORTADOR DE INSUFICIÊNCIA CARDÍACA: UM ESTUDO DE CASO - LIMA, CAMILA D. O. D. C.; WINKEMALNN, ELIANE R.; RAHMEIER, LAURA; BOFF, MARCOS A.; CRUZ, VIVIANE E. D. (Salão do Conhecimento, 2013)
Resumo